2023
DOI: 10.1038/s41598-023-35944-5
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin reduces arrhythmogenic effects in rat neonatal and human iPSC-derived cardiomyocytes and improves cytosolic calcium handling at least partially independent of NHE1

Abstract: The antidiabetic agent class of sodium-glucose cotransporter 2 (SGLT2) inhibitors confer unprecedented cardiovascular benefits beyond glycemic control, including reducing the risk of fatal ventricular arrhythmias. However, the impact of SGLT2 inhibitors on the electrophysiological properties of cardiomyocytes exposed to stimuli other than hyperglycemia remains elusive. This investigation tested the hypothesis that the SGLT2 inhibitor empagliflozin (EMPA) affects cardiomyocyte electrical activity under hypoxic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
3
2
0
Order By: Relevance
“…SGLT2i treatment increased the expression of connexin 43, which was accompanied by a significant shortening of the QT interval, highlighting SGLT2i as a treatment option for malignant re-entry arrhythmias in CKD [ 7 , 106 ]. These findings are in line with data from Dos Santos et al, who demonstrated APD duration normalization by SGLT2i after hypoxia-induced APD prolongation in iPSC [ 107 ]. Increased late sodium current (I Na ) is a well-known mechanism of prolonged APD, with an increased risk of EADs [ 108 ] leading to ventricular arrhythmia.…”
Section: Characteristics Of Chronic Kidney Diseasesupporting
confidence: 92%
“…SGLT2i treatment increased the expression of connexin 43, which was accompanied by a significant shortening of the QT interval, highlighting SGLT2i as a treatment option for malignant re-entry arrhythmias in CKD [ 7 , 106 ]. These findings are in line with data from Dos Santos et al, who demonstrated APD duration normalization by SGLT2i after hypoxia-induced APD prolongation in iPSC [ 107 ]. Increased late sodium current (I Na ) is a well-known mechanism of prolonged APD, with an increased risk of EADs [ 108 ] leading to ventricular arrhythmia.…”
Section: Characteristics Of Chronic Kidney Diseasesupporting
confidence: 92%
“…We then demonstrated positive actions on indicators of cardiac hypertrophy and systolic function within the same hearts. This complemented previous findings in rats with mineralocorticoid-induced hypertension 21 , as well as recent suggestions from cardiomyocyte-level findings implicating electrophysiological effects in SGLT2i cardioprotective actions 22 . Finally we demonstrated actions on hypertrophic and contractile changes and on action potential waveform, intracellular Ca 2+ homeostasis and ventricular arrhythmogenicity.…”
Section: Introductionsupporting
confidence: 89%
“…Together these findings in the murine TAC experimental platform thus complement experimental studies in diabetic rats, high-fat-diet db/db mice and myocardial ischemic models. They further extend those earlier cellular level studies using the TAC experimental platform in isolated and or iPSC-derived ventricular cardiomyocytes bearing on APD 7 , 8 and I NaL 8 , 20 , 22 , and alterations in Ca 2+ homeostasis 8 , 11 , 12 reflecting CaMK-II mediated 11 , 13 actions on Ca 2+ signaling proteins including ryanodine receptor type II (RyR2) and phospholamban (PLN) 8 , 11 , 12 , 14 , 15 . Such cellular parameters translate to the level of intact hearts, in the form of the empagliflozin-induced rescues of compromised systolic function, ventricular hypertrophy, electrophysiological and intracellular Ca 2+ homeostatic changes, and arrhythmogenicity.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this respect, SGLT2 inhibitors are now widely used in treating heart failure with or without DM2. Preclinical and retrospective human studies have recently suggested that SGLT2 inhibitors have an antiarrhythmic effect on atrial brillation and ventricular arrhythmias(Gao, Xue, et al, 2022).Silva dos Santos et al demonstrated that empagli ozin reduced arrhythmogenic events via enhancing [Ca 2+ ] transient recovery and improving relaxation kinetics in rat and human cardiomyocytes under hypoxia(Silva et al, 2023). In an animal study, the antiarrhythmic effects of empagli ozin were investigated in a model of global ischemia-reperfusion in rabbits.…”
mentioning
confidence: 99%